An Exploratory Study of High Resolution Computed Tomography of Temporal Bone in Chronic Otitis Media - Pathak, Manish Raj; Gautam, Mahesh; Acharya, Alina; Khanal, Bipin; Pathak, Yagya Raj; Tiwari, Sagar (Nepalese Journal of Radiology, 2022)
Introduction: Among various modalities used in the evaluation of chronic otitis media, HRCT of the temporal bone is the most reliable and valuable imaging modality as it provides excellent anatomic information. It can display minute anatomical and pathological details by providing a direct visual window into the temporal bone. Methods: This is a prospective cross-sectional study done at the department of Radiodiagnosis and imaging of Birat Medical College, Teaching hospital over 1 year with a total of 50 patients enrolled in the study. The findings were compared with the post-operative findings and data were entered. HRCT was done on 64 slices of multidetector CT scan. Sensitivity, specificity, positive predictive value, negative predictive value and accuracy of various parameters were calculated. Results: Out of 50 patients were enrolled in this study. Among them 52%(26) were females and 48%(24) were males. HRCT showed 100% sensitivity for the lateral semicircular canal and sigmoid plate erosion. The sensitivity and specificity of cholesteatoma were 79.06% and 42.85% respectively. It also offered a sensitivity of 75% and 95% for the erosion of the facial nerve canal and tegmen tympani respectively Conclusions: High-resolution computed tomography is a reliable diagnostic tool for the pre-operative evaluation of chronic otitis media. It helps the operating surgeon to evaluate the anatomical extent of the disease process and aids in the surgical approach that helps prevent probable complications during surgery